The Effect of Organizational Climate, Communication, and Organizational Commitment On Generation Z Performance - Annisa, Nenden Nur; Wardhani, Diana Pramudya; Wijayanti; Putri, Lailatul Anzil Hidayah (CV ODIS, 2023)
Performance is work behaviour that has been achieved in completing the tasks and responsibilities given within a certain period. Factors that affect performance are organizational climate, communication and organizational commitment. The purpose of this study was to examine the effect of organizational climate on employee performance, to examine the effect of communication on employee performance, and to examine the effect of organizational commitment on employee performance. The population in this study were all employees of PT. Tjengkeh Plantation Kendal Selokaton Plantation 120 employees. The sampling technique in this study used a purposive sampling technique with the criteria of sample employees taken being contract employees and employees aged at least 18-28 years, or at least the year of birth in 1995. Data collection used a questionnaire with alternative answer choices using a Likert scale that had been tested and met the requirements of validity and reliability. The analytical tool used is multiple linear regression. The results of the data analysis show that organizational climate has a positive and significant effect on employee performance, communication has a positive and significant effect on employee performance, and organizational commitment has a positive and significant effect on employee performance.